Responses of the macrobenthic community to the Dalian Bay oil spill based on co-occurrence patterns and interaction networks. (October 2021) - Gu, Yanbin; You, Yuxi; Thrush, Simon; Brustolin, Marco; Liu, Yu'an; Tian, Shuang; Ye, Jinqing; Jia, Hao; Liu, Guize
Abstract: On July 16, 2010, a pipeline explosion spilled 1500 tons of crude oil into the Port of Dalian, China. To identify taxa responses to the spill, we exploited seven years of monitoring data to examine the co-occurrence of taxon pairs and the variation of the macrobenthic community. Non-parametric correlation analysis was used to construct interaction networks of relationships between oil spill contaminants and macrobenthic taxa. We observed that the impacted macrobenthic community not restored before 2016. The tolerance/sensitivity of taxa was inconsistent with the studies of oil impacts in other locations. We suggest revision of the ecological group classification of Sabellidae, Lumbrineridae, Terebellidae, Sternaspidae, and Spionidae. The variation in the frequency of coexistence indicates the potential impact of oil spill pollution on resource occupation. The interaction network involving macrobenthic families and stressors associated with the oil spill highlights how different macrobenthic families respond to different combinations of stressors. Highlights: The Macrobenthic community structure impacted by Dalian Bay oil spill not restored until 2016. The tolerance/sensitivity of some taxa in this study was inconsistent with other locations. The variation in taxa coexistence indicates the potential impact of oil spill pollution on resource occupation. The interaction network highlights how different macrobenthic families respond to different combinations of stressors.